2018
DOI: 10.1177/1077559518814364
|View full text |Cite
|
Sign up to set email alerts
|

Connecting Child Maltreatment Risk With Crime and Neighborhood Disadvantage Across Time and Place: A Bayesian Spatiotemporal Analysis

Abstract: Child maltreatment is a major public health problem. Although maltreatment rates vary over time and are influenced by neighborhood characteristics, the unique effects of crime and disadvantage on risk are not well understood. This study utilized a Bayesian spatio-temporal approach to examine risk factors for substantiated child abuse and neglect over a 9-year period across zip codes in Davidson County, Tennessee. Risk for child sexual and physical abuse decreased from 2008 to 2016. In contrast, risk for child … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 69 publications
1
19
0
2
Order By: Relevance
“…Many of the features of the environment discussed throughout this paper that impact IPV victimization can be applied-even if tailoring is needed-to other forms of interpersonal victimization, as the theoretical mechanisms likely operate similarly. Some work has already been done, including to examine neighborhood effects on child abuse (e.g., Morris et al, 2019) and dating violence (Rothman et al, 2011). However, more expansion could be done, for instance, regarding neighborhood conditions that reduce the likelihood of reporting or detecting IPV, intervening on it, and/or supporting victims in the aftermath of victimization are likely also applicable to sexual abuse, human trafficking, and repeat interpersonal victimization.…”
Section: Expansion To Sexual Abuse Human Trafficking and Repeat Victimizationmentioning
confidence: 99%
“…Many of the features of the environment discussed throughout this paper that impact IPV victimization can be applied-even if tailoring is needed-to other forms of interpersonal victimization, as the theoretical mechanisms likely operate similarly. Some work has already been done, including to examine neighborhood effects on child abuse (e.g., Morris et al, 2019) and dating violence (Rothman et al, 2011). However, more expansion could be done, for instance, regarding neighborhood conditions that reduce the likelihood of reporting or detecting IPV, intervening on it, and/or supporting victims in the aftermath of victimization are likely also applicable to sexual abuse, human trafficking, and repeat interpersonal victimization.…”
Section: Expansion To Sexual Abuse Human Trafficking and Repeat Victimizationmentioning
confidence: 99%
“…Previous studies have illustrated the complex impacts of caregiver distress and shared traumatic exposure on children's psychosocial functioning, with evidence that increased caregiver distress following disaster predicts greater child stress ( Kerns et al, 2014 ; Morris et al, 2019 ) and risk of child maltreatment ( Curtis et al, 2000 ; Lawson et al, 2020 ; Seddighi et al, 2021 ). In particular, many recent studies have highlighted the psychological effects of COVID-19 on children ( Babore et al, 2021 ; Bhogal et al, 2021 ; Jiao et al, 2020 ; Korte et al, 2021 ; Kudinova et al, 2021 ), with important insights on the relationship linking children's well-being with that of their caregivers ( Babore et al, 2021 ; Bate et al, 2021 ; Kerr et al, 2021 ; Uccella et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Farrell et al analyzed national representative data including child abuse fatalities and population statistics for the period 1999—2014 in the US and found that children living in counties with the highest poverty concentration were significantly associated with a higher rate of child abuse fatalities as compared to counties with the lowest poverty concentration ( Farrell et al, 2017 ). A study by Morris et al using data for 31 zip codes over the period 2011—2014 in the US showed that poverty was associated with an increased risk of all child maltreatment subtypes, and unemployment rate was associated with child neglect ( Morris et al, 2019 ). Schneider et al showed that economic uncertainty, measured by unemployment rate and the Consumer Sentiment Index, was a significant risk factor for child abuse and neglect ( Schneider et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%